Nicotine-mediated OTUD3 downregulation inhibits VEGF-C mRNA decay to promote lymphatic metastasis of human esophageal cancer - Meng Wang (Nature Portfolio, 2021)
The mechanism of how VEGF-C is regulated to promote lymphatic metastasis of oesophageal cancer is unclear. Here the authors show that nicotine prevents the mRNA decay of VEGF-C mRNA and promotes lymphatic metastasis by downregulating deubiquitinase OTUD3 and RNA binding protein ZFP36.